Hormesis method for increasing oat straw with a view to viability of direct-seeding systems - Felix Tavares, Leandro Augusto; Gomes Sousa, Saulo Fernando [UNESP]; Silva Correia, Tiago Pereira da [UNESP]; Arbex Silva, Paulo Roberto [UNESP]; Velini, Edivaldo Domingues [UNESP] (Univ Federal Ceara, Dept Geol, 2015)
In conservation agriculture, mainly under direct seeding, maintaining the vegetation ground cover is essential, since this serves as a reservoir of nutrients which are slowly released to plants by microorganisms. Some authors have sought to study increases in the amount of straw in the soil, in addition to slowing down the process of decomposition, with hormesis being one of the techniques used. This technique states that all chemical substances are both poisonous and nonpoisonous, with only the dosage determining whether they are lethal or not. This study aimed to evaluate the dry weight and agronomic characteristics of a crop of black oat subjected to hormesis. The experimental design was of randomised blocks, with 12 treatments and 4 replications, giving a total of 48 experimental lots. The treatments were: Haloxyfop-R Methyl Ester at dosages of 0.625, 1.25 and 2.50 g ha(-1); Glyphosate at dosages of 12.50, 25.00 and 50.00 g ha-1; 2,4-D dimethylamine salt at dosages of 100.00, 200.00 and 300.00 g ha(-1); Alterbane at a dosage of 500.00 g ha(-1); Salicylic acid at a dose of 100 g ha(-1); and a control. It was concluded that for the subdosages under test, the herbicides 2,4-D at medium dosage and Verdict at low dosage were shown to be the best treatments for conserving straw as ground cover under direct seeding.

Na agricultura conservacionista, principalmente no plantio direto, a manutenção da cobertura vegetal sobre o solo é essencial, pois esta funciona como reservatório de nutrientes que lentamente serão liberados para as plantas através de microrganismos. Alguns autores têm procurado estudos para aumentar a quantidade de palha presente no solo, além de desacelerar seu processo de decomposição, sendo uma das técnicas utilizadas a hormesis. Essa técnica diz que todas as substâncias químicas são veneno e não veneno, o que faz dela letal ou não, é apenas a dosagem. O trabalho teve como objetivo avaliar a matéria seca e as características agronômicas da cultura da aveia preta submetida à hormesis. O delineamento experimental foi em blocos casualizados com 12 tratamentos e 4 repetições, totalizando 48 parcelas experimentais. Os tratamentos foram: Haloxifope-R Éster Metílico na dosagem de 0,625; 1,25 e 2,50 g ha-1, Glyphosate na dosagem de 12,50; 25,00 e 50,00 g ha-1, (2,4-D) Sal Dimetilamina na dosagem de 100,00; 200,00 e 300,00 g ha-1, Alterbane na dosagem de 500,00 g ha-1, Ácido salicílico na dosagem de 100 g ha-1 além de uma testemunha. Concluiu-se que nas subdosagens testadas, os herbicidas 2,4 D na dosagem média e Verdict na dosagem baixa, apresentaram-se como melhores tratamentos para a conservação de palha no solo sob plantio direto.
Método hormesis para o aumento da palhada de aveia preta visando à viabilidade do sistema de plantio direto
Keywords: Sustainability; Vegetation cover; Direct-seeding systems; Sustentabilidade; Cobertura vegetal; Sistemas de plantio direto